-3(3+5x)=-112

Simple and best practice solution for -3(3+5x)=-112 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(3+5x)=-112 equation:


Simplifying
-3(3 + 5x) = -112
(3 * -3 + 5x * -3) = -112
(-9 + -15x) = -112

Solving
-9 + -15x = -112

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + -15x = -112 + 9

Combine like terms: -9 + 9 = 0
0 + -15x = -112 + 9
-15x = -112 + 9

Combine like terms: -112 + 9 = -103
-15x = -103

Divide each side by '-15'.
x = 6.866666667

Simplifying
x = 6.866666667

See similar equations:

| 18uv^2w^3+30u^6v^5= | | -6(5+x)=24 | | 3y-6+y+40=8y+40-6y | | No-r=p | | 4(5-x)(x+6)=0 | | 0P=30 | | 6x-(5-4x)=5 | | (x^2-6x+5)(7x-4)= | | 7x+8=108-3x | | 45-7x=-31-11x | | 3(1-x)=-3(x+2) | | (7y^2+5y-6)(7y^2+4y+1)= | | 8+6x=-x-55 | | 2(3+5x)+2(5x+3)=92 | | 3(-2x-3)-2=10-3x | | 6x-3(5x+4)=-3(3x+4)+6 | | 6+6x=-7x+123 | | 3f-5d=10 | | -1-3x+7x=-9 | | -6(x-1)=3(2-x)+4x | | 5x+25=3x-15 | | (3x-2)(7x^2-x-6)= | | -6y=x+21 | | y+7=70 | | 6-7=5-6x | | -32+6x=10x+56 | | 3y-17=2x+2 | | 20=n^4 | | (-27y^9z^6)(2x^3y^3z^2)= | | -5+2[10b-2]=31 | | -1+6x=3x+32 | | 5x-9+5x=71 |

Equations solver categories